(untitled) (Shanti Journal, 2023)
This article explores the satisfaction of the teachers who are working in different public and private schools in Kathmandu Metropolitan City. The article aims to identify the factors that satisfy the teachers so that they retain in the school for a longer period of time. The participants of this study were purposively selected. Collecting questionnaires as the means of data generation, this article finds out insights from 194 teachers who have been in the teaching field for more than a year. Most of the teachers found enjoyment in their work, regardless of government, private or community schools. They pointed out the importance of the role of the supervisor as well as the opportunity to attend the training in the job satisfaction. The research shows that overall enjoyment of job depends on the satisfaction with the benefits provided to the respondents.